Reaksi Pasar Terhadap Publikasi Laporan Keuangan Perusahaan Farmasi di Masa Pandemi Covid-19 - Puspita Dewi, Putu Diah Meilani; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p20, 2023)
The Covid-19 pandemic generally has an impact on decreasing stock prices, but pharmaceutical stock prices have actually increased. The research aims to find out the market reaction or response as shown through the average difference in abnormal returns before and after the publication of the 2020-2021 financial reports on the IDX. The population uses all pharmaceutical industry companies on the IDX during 2020-2021. Sampling using nonprobability sampling method through purposive sampling technique. The hypothesis test was carried out using a paired sample t-test and the Wilcoxon signed rank test, in order to test the results of differences in the average abnormal returns before and after the publication of the financial statements. The results showed that there was no market reaction as seen from the absence of an average difference in abnormal returns before and after the publication of the pharmaceutical industry's financial reports on the IDX. This indicates that published financial reports do not influence investors' perceptions in making decisions. Keywords: Event studies; Abnormal return; Covid-19